Genomic copy number variations: A breakthrough in our knowledge on schizophrenia etiology? - Hosak, Ladislav; Silhan, Petr; Hosakova, Jirina (Neuro endocrinology letters, 2012)
OBJECTIVES: The term "copy number variation/variant" (CNV) denotes a DNA sequence with a magnitude of 1 kb at least which is differently represented among individuals based on its deletion or duplication. Since 2008, multiple studies have reported copy number variations in schizophrenia, and they seem to fill in a gap in our knowledge on the genetic background of schizophrenia. The aim of this review is to sum up the current findings related to CNVs in schizophrenia in order to facilitate further research. METHODS: We searched the PubMed computer database using the key words "schizophrenia AND CNVs" on 26th October 2011. Out of 91 obtained results, we selected the references based on their relevance. RESULTS: The CNVs at genome loci 1q21.1, 2p16.3, 3q29, 15q11.2, 15q13.3, 16p13.1 and 22q11.2 were associated with schizophrenia most frequently. The data provide evidence for low prevalent, but highly penetrant CNVs associated with schizophrenia. CNV deletions show higher penetrance than duplications. Larger CNVs often have higher penetrance than smaller CNVs. Although the vast majority of CNVs are inherited, CNVs that have newly occurred as de novo mutations have more readily been implicated in schizophrenia. De novo CNVs may be responsible for the presence of schizophrenia in only one of the two monozygotic twins, who otherwise have identical genomes. CONCLUSION: Identifying CNVs in schizophrenia can lead to changes in the treatment and genetic counselling. Our knowledge on the genetic background of neurodevelopmental disorders may also reduce stigma in schizophrenia.
Keywords: schizofrenie; Schizophrenia; Genome-Wide Association Study; Genetic Predisposition to Disease; lidé; DNA Copy Number Variations; variabilita počtu kopií segmentů DNA; genom lidský; Humans; genetická predispozice k nemoci; Genome, Human; celogenomová asociační studie